Calculation of the Entropy of random coil polymers with the hypothetical scanning Monte Carlo Method - White, Ronald P. (2005)
Hypothetical scanning Monte Carlo (HSMC) is a method for calculating the absolute entropy, S and free energy, F from a given MC trajectory developed recently and applied to liquid argon, TIP3P water and peptides. In this paper HSMC is extended to random coil polymers by applying it to self-avoiding walks on a square lattice – a simple but difficult model due to strong excluded volume interactions. With HSMC the probability of a given chain is obtained as a product of transition probabilities calculated for each bond by MC simulations and a counting formula. This probability is exact in the sense that it is based on all the interactions of the system and the only approximation is due to finite sampling. The method provides rigorous upper and lower bounds for F, which can be obtained from a very small sample and even from a single chain conformation. HSMC is independent of existing techniques and thus constitutes an independent research tool. The HSMC results are compared to those obtained by other methods, and its application to complex lattice chain models is discussed; we emphasize its ability to treat any type of boundary conditions for which a reference state (with known free energy) might be difficult to define for a thermodynamic integration process. Finally, we stress that the capability of HSMC to extract the absolute entropy from a given sample is important for studying relaxation processes, such as protein folding.